The Use of Liraglutide in Obese Patients With COVID-19: A Case Report - Hanada, Taliê Zanchetta Buani (J Endocr Soc, 2021)
Introduction: In December 2019, a new type of coronavirus was discovered in Wuhan, China, characterized by a picture of atypical pneumonia composed of fever, dry cough and progressive dyspnea. Autopsy analyzes of patients with Covid-19 were performed, and hyperactivation of cytotoxic T cells was observed, suggesting an increase in humoral-type immunological signaling, where interleukin 6 (IL-6) is a mediator present that can fit as a potential critical agent for exacerbation of inflammatory conditions. In addition, not only interleukin-6, but also serum C-reactive protein (CRP) and ferritin have been recognized as strong predictors of COVID-19 severity. Recent studies have shown that the use of liraglutide has antioxidant and anti-inflammatory effects in vitro. Thus, the present case report discusses the possible anti-inflammatory properties of the antidiabetic drug liraglutide (Saxenda), in Covid-19. Clinical Case: JCMS, 45 years, male, married, obese grade 2 (BMI: 38.2), sought medical service on August 18, 2020, bringing a positive result of the RT-PCR test for Covid-19, performed in last day. The patient was in good general condition, reporting mild headache and adynamia. He was prescribed to start a treatment with Saxenda (6mg/ml - started 0.6mg/day at week 1, with a gradual increase up to 3mg/day at week 5); Jardiance (25mg / day); Fluimicil (600mg); Ivermectin (6mg) and Colchicine (0.5mg every 12 hours). In addition, collection of laboratory tests was requested. Examination results: IL6: <1.5 pg/mL; Ferritin: 819 ng/ml; C-reactive protein: 5.1mg/L. On August 24, the patient was tachycardic (HR 120–140 bpm) associated with headache and fever (38 °C). Azithromycin (500mg), dexamethasone (4mg) and dipyrone (1g) were prescribed. Collection of laboratory tests was requested. Examination results: IL6: 9.3 pg/mL; Ferritin: 1085 ng/ml; C-reactive protein:23.9mg/L. On September 3, the patient was in good general condition, eupneic, afebrile, with no complaints to declare. On September 6, the collection of laboratory tests was requested. Examination results: IL6: <1.5 pg/mL; Ferritin: 687 ng/ml; C-reactive protein: 1.7mg/L. Conclusion: Based on the described report, it is possible to observe a good clinical and laboratory evolution of the patient with Covid-19 who, among the drugs used, made use of liraglutida. Diabetes and obesity are considered significant risk factors for morbidity and mortality by COVID-19, since they are a condition of low-grade chronic inflammation and in these conditions, inflammatory markers such as CRP, IL-6 and ferritin have strong signs of alteration. Thus, the possible beneficial effect of the administration of liraglutide in obese patients is highlighted, as a potential anti-inflammatory effect, especially in the COVID-19 era.